Preparing teachers for inclusive education (2012)
The success of inclusive education in any context depends upon many factors. Teachers themselves are critical elements in ensuring the quality of students’ inclusion in the school environment. Teachers have direct interaction with students and play a critical role in determining students’ experiences in the classroom on a daily basis. Special attention must be paid not only to the classroom teachers who have the skills but also to the support needed to provide quality education to children with diverse learning needs. This requires the collaboration of classroom teachers, special education teachers, school principals, education officers and policy makers. This paper indicates that preparing teachers with essential knowledge and skills for inclusive education requires the commitment of all stakeholders. This paper further stresses that preparing teachers does not simply mean providing prospective teachers with inclusive education skills; it also means providing training and support for existing teachers as well. It is also the position of this paper that building capacity for inclusive education should include awareness raising activities as well as integrated pre-service and in-service teacher training programmes to ensure that teachers are aware, ready and willing to implement inclusive education properly.